Virtue’s cosmos Enaction as an anthropology of eschatology - NASIR, MUHAMMAD ALI (My University, 2022)
© 2022 The Society for Ethnographic Theory. All rights reserved.As youngsters in a Pakistani megacity participate in a reading group to discuss the end of time by looking at the eschatological prophecies in Islamic religious sources, they come to relate apparently trivial political actions such as wall-painting, placard-holding, and pamphlet-distributing to the question of justice. We suggest in this article that this complex phenomenon can be best understood through the concept of enaction, as ethical actions are seen to enact a context suffused with political and cosmological considerations. Accordingly, our discussion positions itself against those works in the anthropology of ethics that primarily view such ethical actions in terms of self-cultivation.
Keywords: Sosyal ve Beşeri Bilimler; Antropoloji; Social Sciences and Humanities; Anthropology; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; ANTROPOLOJİ; Arts & Humanities (AHCI); ARTS & HUMANITIES; ANTHROPOLOGY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; anthropology of ethics; eschatology; Islam; justice; self; enaction; ETHICS; AUTHORITY; FATALISM; DESTINY; LABOR; Anthropology of ethics; Enaction; Eschatology; Justice; Self